Molecular Study of Aspirjillus Ochraceus Isolated from Air Condition Unite in Muthanna City - Maysoon M. Al-Jobouri, Ebtesam Th. Jeaz (Pakistan Journal of Medical & Health Sciences, 2022)
The current study dealt with the isolation and diagnosis of fungi contaminating air condition AC in the laboratories of the Technical Institute in Al-Muthanna, the laboratories of the College of Agriculture at the University of Al-Muthanna during the period from August 14/08/2020 to 28/2/2022 , This study included isolating and diagnosing a fungus from the refrigeration systems and the total number of samples is 400 isolated samples from the refrigeration systems in the city of Muthanna, After the sample was diagnosed phenotypically and microscopically on the medium of Sabouraud Dextrose Agar, it was molecularly diagnosed after extracting DNA for five isolates from the fungus, where all the isolates showed a positive result373bp for molecular.